2007
DOI: 10.1093/molehr/gam087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the evolution of chromosome abnormalities in human embryos from Day 3 to 5 using CGH and FISH

Abstract: The use of interphase fluorescent in situ hybridization (FISH) has shown that a large number of human embryos exhibit chromosomal abnormalities in vitro. The most common abnormality is mosaicism which is seen in up to 50% of preimplantation embryos at all stages of development. In this study, comparative genomic hybridization (CGH) was used to analyse 1-2 cells biopsied on Day 3 of development while the rest of the embryo was cultured until Day 5. Embryos were spread on Day 5 and analysed by FISH using probe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 55 publications
4
52
0
Order By: Relevance
“…Approximately 30% of the embryos contained a segmental aneuploidy including simple losses or gains of p-or q-terminal chromosome fragments, but again more complex segmental aneuploidies were detected consisting of a deletion of a terminal part of a chromosome and a duplication of the remaining part of that chromosome. Daphnis et al [2008] further analyzed and confirmed part of these segmental aneuploidies by FISH. Rius et al [2010] analyzed 157 blastomeres by a short CGH protocol from 22 day 4 embryos following FISHbased preimplantation genetic aneuploidy screening that was offered to 8 couples with advanced maternal age.…”
Section: Single-cell Cgh Studiesmentioning
confidence: 87%
See 3 more Smart Citations
“…Approximately 30% of the embryos contained a segmental aneuploidy including simple losses or gains of p-or q-terminal chromosome fragments, but again more complex segmental aneuploidies were detected consisting of a deletion of a terminal part of a chromosome and a duplication of the remaining part of that chromosome. Daphnis et al [2008] further analyzed and confirmed part of these segmental aneuploidies by FISH. Rius et al [2010] analyzed 157 blastomeres by a short CGH protocol from 22 day 4 embryos following FISHbased preimplantation genetic aneuploidy screening that was offered to 8 couples with advanced maternal age.…”
Section: Single-cell Cgh Studiesmentioning
confidence: 87%
“…Low-resolution genome-wide surveys of single human blastomeres, using metaphase comparative genomic hybridization (CGH), for the first time revealed, in addition to whole chromosome aneuploidies, the occurrence of segmental chromosome imbalances in approximately 7-32% of the embryos [Voullaire et al, 2000[Voullaire et al, , 2002Wells and Delhanty, 2000;Wilton et al, 2003;Daphnis et al, 2008;Rius et al, 2010] ( table 1 ). Voullaire et al [2000] detected a postzygotic breakage of chromosome 2 at q31 and of chromosome 10 at q11.2 in 1 out of 12 good quality embryos (8%) yielding cells with reciprocal loss and gain of the 2 fragments from each chromosome.…”
Section: Single-cell Cgh Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosome losses and gains, presumably due to anaphase lagging, are a common feature of mosaicism in human preimplantation embryos [e.g. Daphnis et al, 2008]. Currently, it is still unclear whether mitotic nondisjunction is a normal phenomenon in early human preimplantation development or mainly related to suboptimal culture conditions in assisted reproduction.…”
Section: Epigenetic Alterations: a New Mechanism Of Aneuploidy Inductmentioning
confidence: 99%